Exchange Bias Between van der Waals Materials Tilted Magnetic States and Field-Free Spin-Orbit-Torque Switching - Cham, Thow Min Jerald (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.